Pro-thrombotic effect of exercise in a polluted environment: a P-selectin- and CD63-related platelet activation effect - Wauters, Aurélien; Esmaeilzadeh, Fatemeh; Bladt, Sandrine; Beukinga, Ingrid; Wijns, Walter; Borne, Philippe van de; Pradier, Olivier; Argacha, Jean-François (Thrombosis and Haemostasis, 2015)
Exposure to diesel exhaust is an important cardiovascular risk factor and may promote atherothrombotic events. Some data suggest that polluted air exposure could affect haemostasis through platelet activation. The aim of the study was to investigate the effects of acute exposure to diesel exhaust on platelet activation and platelet function. We tested the hypothesis in a randomised, crossover study in 25 healthy men exposed to ambient and polluted air; 11 of the subjects also performed exercise during exposure sessions. Platelet activation was evaluated by surface expression of CD62P (P-selectin) and CD63 (dense granule glycoprotein) using flow cytometry of labelled platelets. Platelet function was measured using the PFA-100 platelet function analyser and by Multiplate whole blood impedance platelet aggregometry. Acute diesel exhaust exposure had no effect on platelet activation at rest, but exercise in polluted air increased the collagen- induced expression of CD62P and CD63 (both p< 0.05). The increase in the expression of CD62P and CD63 was related to the total amount of PM2.5 inhaled during the exercise sessions (r=+0.58 and +0.60, respectively, both p< 0.05). Platelet aggregation was not impaired after polluted air exposure at rest or during exercise. In conclusion, in healthy subjects, diesel exhaust exposure induces platelet activation as illustrated by a dose-response increase in the release of CD62P and CD63. This platelet priming effect could be a contributor to the triggering of atherothrombotic events related to air pollution exposure.
Keywords: Environmental (risk) factors; atherothrombosis; platelet glycoproteins